Mineral Exploration at the Kimmeria Fe-Cu Skarn Deposit, N. Greece: Reassessment and New Perspectives Focusing on the CRMs - Michalis Fitros; Constantinos Mavrogonatos; Marianthi Anastasatou; Adamantia Chatziapostolou; Konstantinos Laskaridis; Petros Karmis; Magdalini Angeli; Dimitrios Tsouvalas; Alexandros Liakopoulos; Dimitrios Tarenidis; Vasiliki Angelatou (Materials Proceedings, 2024)
Following the worldwide increasing demand for Critical Raw Materials (CRMs), the Hellenic Geological Survey (HSGME) implemented a national project focused on the re-evaluation of certain Public Mining Areas in Greece. In this framework, exploration activities, including geological mapping, and mineralogical, geochemical, and geophysical studies, revealed significant mineralization targets which possibly host elevated contents of certain CRMs in the Kimmeria Fe skarn deposit. The mineralization is related to the contact metamorphic aureole of the Oligocene Xanthi pluton. Various skarn minerals form the following paragenetic zones in order of decreasing temperature: (i) garnet–wollastonite, (ii) garnet–clinopyroxene, (iii) garnet–epidote, and (iv) vesuvianite–scapolite. The skarn deposit consists of magnetite-rich ore occurring along with sulfides (chalcopyrite, pyrite, bismuthinite, and molybdenite), scheelite, minor sulfosalts (aikinite, wittichenite, and cubanite) and native elements (Au and Bi). Bulk-rock geochemical analyses yielded significant values, as follows: Fe2O3, up to 58 wt%; Cu, up to 6.6 wt%; Bi, up to 1100 ppm; W, up to 670 ppm; V, up to 200 ppm; Mo, up to 200 ppm; and Au, up to 2.1 g/t. Soil and stream sediment geochemistry reveals spatial and linear trends for certain groups of associated elements (i.e., Fe2O3-Cu-Bi-W and Mo-W-Zn). These trends reflect the surficial distribution of mineralized zones and imply the existence of partially unexposed mineralization in the western part of the study area, a fact also supported by geophysical evidence. A preliminary drilling project has been proposed to evaluate the qualitative characteristics of the deeper parts of the mineralization, investigate buried ore zones in the western part, and overall, reassess the economic potential of the deposit.